About Effect of Hydroelectric Construction on Some Features of Fish Biology - Matrosova Inga Vladimirovna (EDP Sciences, 2021)
Restructures in the communities of hydrobionts take place for the rivers with abrupt changes in hydrography and hydrological regime, as a result of flow regulation. They require long-term monitoring to develop preventive measures to avoid negative consequences and to restore the river ecosystem. Some biological characteristics of the broad whitefish (Coregonus nasus) have been studied during spawning migration in the upper reaches of the Yenisei River. The limiting values of the fish length were higher in 2016, and the average - in 2013. In 2013, the sampling frame consisted of fish of 51-55 cm in size, in 2014 and 2016. - 41-45 cm. In 2013, most of the fish in the catches were aged from 6+ to 11+ years, in 2014 - from 8+ to 10+ years, in 2016 from 8+ to 11+ years. The gender ratio was close to 1:1; most of the individuals had gonads at maturity stage III.